Heavy metals in three varieties of Solanum tuberosum L. (potato) expanded in the wholesale market of Santa Anita (Lima-Peru) - López D., Leavit K. (2020)
Vegetables foods are contaminated with heavy metals by different routes, being a risk to the health of the consumer. In this study was performed the quantification of heavy metals cadmium (Cd), lead (Pb), mercury (Hg) and arsenic (As) in fresh tubers of three potato varieties of Solanum tuberosum L. (potato): canchan, huayro and yellow. The samples were randomly collected from 15 stalls in the wholesale market of Santa Anita, province of Lima (Lima - Peru) all from the province of Ambo, department of Huánuco (Peru); 15 samples were collected from each variety with a total of 45 samples. The quantification of Cd and Pb was performed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS), meanwhile, for the quantification of Hg and As, was used Atomic Fluorescence Spectrometry (AFS).. The Hg concentration ranged from 0,0983 to 0,2594 mg / Kg; Cd from 0,0073 to 0,0287 mg / Kg; Pb from 0,0600 to 0,1018 mg / Kg and As from 0,0003 to 0,0004 mg / Kg. The concentration of Hg in the three varieties far exceeded the maximum limit allowed (MLA) by the European Union (0,02 mg / Kg), therefore, it constitutes a high risk for the consumer. Cd and As concentrations in the three varieties were found below the MLA by Codex Alimentarius and Mercosur; likewise, the Pb in the canchán and huayro varieties were found below the MLA (0,1 mg / Kg); however, in the yellow variety was found a value slightly higher than the MLA.